The Effect of Using Powtoon Interactive Learning Media to Improve Learning Outcomes in Class X Informatics Subjects at SMK Kesehatan Samarinda - Anisa Permata Sari; Haeruddin; Galih Yudha Saputra (Politeknik Pertanian Negeri Samarinda, 2024)
This study aims to determine the effect of using Powtoon interactive learning media to improve learning outcomes in learning Informatics class X students at SMK Kesehatan Samarinda. This type of research is quantitative, namely experimental research (pre-experimental design) using a one group pretest-posttest design research design, namely an experiment that in its implementation only involves one class as an experimental class without a control class (comparison class). Data analysis used descriptive analysis techniques and inferential analysis techniques. The results of descriptive statistics show that the average student pre-test score is 46.56 and has increased after being treated with an average student post-test score of 80.31. The results of inferential statistical analysis by testing the normality of pre-test and post-test data were normally distributed. The results of hypothesis analysis using the Paired Sample T-Test test, namely significance, obtained a value smaller than 0.05, namely 0.000 <0.05, meaning that there is a difference when the initial test (pre-test) and the final test results (post-test) so that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. The results of the analysis of student learning on the use of Powtoon interactive learning media in Informatics subjects obtained an N-Gain of 0.72 which is included in the high category. This study shows that there is an effect of using Powtoon interactive learning media to improve student learning outcomes in Informatics class X Nursing 2 at SMK Kesehatan Samarinda.